English proficiency among public servant case study: Perbadanan Muzium Melaka (PERZIM) - Alias, Kamaliah; Roslan, Nuur Arfah (2007)
Good organization has brought the name of the country in the eyes of the world. People worldwide will like to visit if they feel comfortable and satisfy with surrounding and service provided. Perbadanan Muzium Melaka (PERZIM) in which responsible to manage and admin the historical museum always receive visitors not only from local but also worldwide. So the study was examined to the usage of English proficiency. A census has been made to 95 staffs at PERZIM as respondents. The staffs’ level of English proficiency was examined. The staffs’ level of English proficiency is at low level. These are result from staffs’ attitude resistance to change and not practically use English in their daily communication. PERZIM’s management and its staffs need to put some effort in order to enhance their English proficiency.